Was Aristotle right about moral decision-making? Building a new empirical model of practical wisdom - Shane McLoughlin; Stephen Thoma; Kristján Kristjánsson (PLoS ONE, 2025)
This article presents the development and validation of the Short Phronesis Measure (SPM), a novel tool to assess Aristotelian phronesis (practical wisdom). Across three studies, using large, nationally representative samples from the UK and US (demographically matched to census data), we employed a systematic and rigorous methodology to examine the structure, reliability, and validity of the SPM. In Study 1a, exploratory factor analysis identified ten distinct, internally reliable components of phronesis , challenging the traditional four-component Aristotelian model. Study 1b confirmed these findings in two additional nationally representative samples from the UK and the US. In Study 1c, the SPM demonstrated strong test-retest reliability over two months. Study 2 used network analysis to uncover interrelations among the components, allowing for the creation of a new and empirically driven neo -Aristotelian model of phronesis . In Study 3, we tested criterion validity, showing phronesis correlates positively with flourishing and predicts flourishing two months later, demonstrating strong predictive validity. Phronesis also correlated with Big 6 and Dark Tetrad personality traits, moral disengagement, and Moral Foundations in expected directions. Importantly, phronesis predicted key outcomes—related to flourishing, moral disengagement, and morally relevant aspects of personality—beyond what Moral Foundations alone explained, with an average increase in predictive power of 13.7% across all outcomes. The SPM is quick to administer (15–20 minutes), making it a valuable tool for researchers and practitioners in psychology, education, and professional ethics. The introduction of the neo-Aristotelian Phronesis Model, and the identification of central phronesis components, offers actionable insights for moral psychologists and moral educators, suggesting areas of focus that could yield broad, positive effects across related traits, providing a significant contribution to both theory and practice.